Aberrant hippocampal gamma oscillations in a mouse model of fragile X syndrome: insights from in vitro slice models - Pollali, Evangelia; Donaire, Daniel Frías; Ángel, Miguel Del; Demiray, Yunus Emre; Lacalle, Sara Enrile; Hollnagel, Jan-Oliver; Annamneedi, Anil; Caliskan, Gürsel (Molecular autism, 2025)
Background: Fragile X syndrome (FXS) is the most common inherited intellectual disability, caused by the loss of fragile X mental retardation protein (FMRP), which regulates neuronal signaling and plasticity. FXS patients and Fmr1 knockout (KO) mice exhibit sensory hypersensitivity, hyperarousal, and hippocampus-dependent learning deficits. Dysregulated metabotropic glutamate receptor (mGluR) and muscarinic acetylcholine receptor (mAChR) signaling, along with reduced kainate receptor (KAR) function, have been implicated in FXS pathophysiology. Activation of these signaling pathways induce gamma-frequency network oscillations hippocampal slices in vitro. However, their specific contribution to aberrant gamma oscillations in FXS remains unclear. Methods: We recorded local field potential (LFP) gamma oscillations in vitro in hippocampal CA3 from wild-type (WT) and Fmr1 KO mice. Oscillations were induced pharmacologically using carbachol (CCh), the group I mGluR agonist dihydroxyphenylglycine (DHPG), or kainate (KA). In addition, we quantified synaptic protein expression of mAChR M1, mGluR1, mGluR5, GluK1, and GluK2-receptors involved in gamma oscillation generation under these conditions. Results: Fmr1 KO slices exhibited increased integrated gamma power (20–80 Hz) in response to DHPG and CCh, suggesting higher network synchronization through mGluR and mAChR pathways. In contrast, KA-induced oscillations showed reduced synchrony and gamma peak power, indicating disrupted network coordination. Aberrant spiking activity during both CCh- and KA-induced oscillations further supports impaired temporal coordination in Fmr1 KO mice. These physiological changes were only partially reflected by altered expression of the corresponding receptor proteins. Limitations: In the current study, we found aberrant gamma oscillation power in in vitro hippocampal slices of Fmr1 KO mice. It remains to be determined whether these oscillatory changes extend to pharmacologically induced gamma oscillations in cortical slice preparations in vitro. Conclusions: Our findings demonstrate that hippocampal gamma oscillations are differentially affected by distinct neuromodulatory pathways in Fmr1 KO mice. Enhanced responsiveness to cholinergic and mGluR activation and reduced coherence of KA-induced rhythms suggest that multiple dysregulated mechanisms contribute to gamma oscillopathies in FXS.